Say no more. - Ryan, Hank Phillippi (Ryan, Hank Phillippi. Jane Ryland novel., 2016)
"Reporter Jane Ryland's entire career is based on discovering secrets. But turnabout is fair play: when Jane witnesses a hit-and-run, it's her turn to provide information, and she does it with her trademark quick thinking, confidence, and skill. But she soon learns she saw more than a car crash- she witnessed the collapse of an alibi. Then a disturbing anonymous message arrives with her mail- SAY NO MORE."